Increased Serum SP-D Level, Neutrophils and Lymphocytes Sputum in Malang Splendid Bird Market Workers - Ratih Dwi Ary Merdekawati; Tri Wahju Astuti; Garinda Alma Duta (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Workers in the bird market have a high risk of exposure in the form of air pollution, pollutant particles including debris / organic dust, loose feathers, insects/ticks, aerosol particles in food, bird excreta (ammonia), various kinds of gram bacteria, fungi and virus. Exposure to particles will stimulate the immune system against harmful pathogens in the form of inflammatory response. An infection or injury will stimulate the secretion of Surfactant protein-D (SP-D) which is a group of collectin (collagen-lectin) with subgroups of the C-type lectin superfamily, together with bovine coglutinin, mannose-binding lectin (MBL), and CL43 protein. This aim of this study was to determine serum SP-D and neutrophil and sputum lymphocyte levels in workers at splendid bird market.Methods: A cross sectional analytic observational study on 35 subjects, analyzed the characteristics of the workers, calculated neutrophil types, lymphocytes on induced sputum and serum SP-D levels using sandwich ELISA.Results: Mean SP-D serum levels in workers in the bird market environment increased (mean SD: 81.39 + 47.656 ng/ml) from normal levels (60 ± 3 ng/ml). There was a significant positive correlation between length of exposure and serum SP-D levels (r: 0.693; p <0.001). There was an average increase in the percentage of neutrophils and sputum lymphocytes (90.71% + 4.04% and 9.17% + 4.42%) compared to normal limit (50.3% + 23.5% and 2.6% + 5.2%).Conclusion: Inhalation exposure in the Bird Market environment can cause an increase in the percentage of neutrophils, sputum lymphocytes and serum SP-D levels in workers that indicate an airway inflammation process, as well as an alleged increase in alveolar wall permeability, damage and regeneration of alveolar epithelial cell type II cells (AEC type II).